The Relationship of Age With Stroke Complications - Widya Arjuni; Achmad Harun; St.Haeriyah Bohari (Sean Institute, 2024)
Stroke is the number one cause of disability and the number three cause of death in the world after heart disease and cancer in both developed and developing countries. In Indonesia, the incidence of stroke from 2013 to 2018 increased by 7% - 11% or 2,120,362 people. The high number of strokes has the potential to increase prevalence in all age groups. The risk of having a stroke increases from the age of 45 years. After the age of 50, every three additional years of age increases the risk of stroke by 11-20%. Risk factors for stroke complications are stroke severity, type of stroke, lesion size, mechanical ventilation, age, gender and history of diabetes. Several literatures have reported that 44%-75% of stroke patients experience at least one complication during inpatient rehabilitation, the most common of which are musculoskeletal pain, fever depression, pressure sores, fall infections, upper gastrointestinal bleeding (UGIB), seizures, nutritional deficiencies. , deep vein thrombosis, development of stroke and pulmonary embolism. Several studies reveal that age can influence the occurrence of certain stroke complications. Symptomatic UGIB and UTI were found to be complications influenced by age.